Reform cinema in Iran : film and political change in the Islamic Republic - Atwood, Blake Robert, 1983- (Film and culture., 2016)
It is nearly impossible to separate contemporary Iranian cinema from the Islamic revolution that transformed film production in the country in the late 1970s. As the aims of the revolution shifted and hardened once Khomeini took power and as an eight-year war with Iraq dragged on, Iranian filmmakers confronted new restrictions. In the 1990s, however, the Reformist Movement, led by Mohammad Khatami and the film industry, developed an unlikely partnership that moved audiences away from revolutionary ideas and toward a discourse of reform. In Reform Cinema in Iran, Blake Atwood examines how new i.